Contribution of Ultra Deep Sequencing in the Clinical Diagnosis of a New Fungal Pathogen Species: Basidiobolus meristosporus - Sitterlé, Emilie; Rodriguez, Christophe; Mounier, Roman; Calderaro, Julien; Foulet, Françoise; Develoux, Michel; Pawlotsky, Jean-Michel; Botterel, Françoise (Frontiers in Microbiology, 2017)
Some cases of fungal infection remained undiagnosed, especially when the pathogens are uncommon, require specific conditions for in vitro growth, or when several microbial species are present in the specimen. Ultra-Deep Sequencing (UDS) could be considered as a precise tool in the identification of involved pathogens in order to upgrade patient treatment. In this study, we report the implementation of UDS technology in medical laboratory during the follow-up of an atypical fungal infection case. Thanks to UDS technology, we document the first case of gastro-intestinal basidiobolomycosis (GIB) due to Basidiobolus meristosporus. The diagnosis was suspected after histopathological examination but conventional microbiological methods failed to supply proof. The final diagnosis was made by means of an original approach based on UDS. DNA was extracted from the embedded colon biopsy obtained after hemicolectomy, and a fragment encompassing the internal transcribed spacer (ITS) rDNA region was PCR-amplified. An Amplicon library was then prepared using Genome Sequencer Junior Titanium Kits (Roche/454 Life Sciences) and the library was pyrosequenced on a GS Junior (Roche/454 Life Sciences). Using this method, 2247 sequences with more than 100 bases were generated and used for UDS analysis. B. meristosporus represented 80% of the sequences, with an average homology of 98.8%. A phylogenetic tree with Basidiobolus reference sequences confirmed the presence of B. meristosporus (bootstrap value of 99%). Conclusion: UDS-based diagnostic approaches are ready to integrate conventional diagnostic testing to improve documentation of infectious disease and the therapeutic management of patients.